Pengaruh Model Pembelajaran Kooperatif Make A Match Terhadap Keaktifan dan Hasil Belajar Siswa Pada Mata Pelajaran IPS - Nazylatul Amanah; Widodo Winarso; Rijal Assidiq Mulyana (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of the cooperative learning model Make a Match on students’ activeness and learning outcomes in Social Studies (IPS). The research employed an experimental method with a one-group pretest-posttest design. The subjects of this study were 20 eighth-grade students at MTs Negeri 2 Cirebon. Research instruments consisted of a learning outcomes test and a student activeness observation sheet. The findings showed that the average pretest score of 71.80 increased to 83.40 in the posttest. Both normality and homogeneity tests met the statistical assumptions, while the independent t-test indicated a significance value of 0.000 < 0.05. This result demonstrates that the application of the Make a Match learning model has a significant effect on students’ activeness and learning outcomes in Social Studies. Therefore, this model can be considered an innovative and enjoyable learning strategy to improve the quality of Social Studies learning in schools.